Ratio Decidendi Penafsiran Klausula Eksonerasi Dalam Perjanjian Baku di Indonesia - Fiona Wiananda Adhyaksanti; Kadek Wiwik Indrayanti (KRTHA BHAYANGKARA, 2023)
The existance of an exoneration clause in a standard contract often causes different interpretations by judges when faced with concrete cases. One interesting decision that has sparked debate was the Malang District Court Decision Number 94/Pdt.G/2017/PN Mlg, where the Defendant has included the prohibition of the exoneration clause in the standard contract. This is unacceptable to the Plaintiff, so the cancellation of the contract is requested. However, the Panel of Judges in their decision stated that they rejected all of the Plaintiff's claims. This study aims to analyze the ratio decidendi of the Malang District Court Decision Number 94/Pdt.G/2017/PN Mlg based on the principle of balance of positions between the parties. The research method used is normative legal research with statutory and case approaches The results of this study indicate that the Panel of Judges has its own perspective which has considered philosophical, juridical, and sociological aspects in its Decision. The main dispute that occurred between the parties was caused by the plaintiff's default and not because of the exoneration clause in the standard contract. However, even though the Panel of Judges rejected the Plaintiff's claim, in the context of the principle of balance in a standard contract, the position of the rights and obligations of the parties has not been realized, both from the beginning of the making of the contract to the implementation of the contract.